Late‐stage Rh(II)‐catalyzed titrene transfer for the synthesis of guaianolide analogs with enhanced antiproliferative activity - Castro, Sebastián Jorge (2021)
A set of new guaianolide derivatives (1–9) was obtained from ludartin, achalensolide, and 11,13-dihydroachalensolide by application of catalytic nitrene transfer reactions. Intermolecular nitrene C(sp3)−H insertions led to the amination of C-1, C-2, and C-10 positions, while alkene aziridination was also observed under these reaction conditions. The antiproliferative activity of natural compounds and their derivatives was evaluated against a panel of human solid tumor cell lines. The results show that an increase in the biological activity was observed following amination at the C-2 position of Ludartin, thereby demonstrating the interest in late-stage C−H amination to improve the bioactivity of natural products.